ANALYSIS OF THE USE OF SUBORDINATING CONJUNCTIONS IN DETIK.COM NEWSPAPER AS A LEARNING RESOURCE FOR GRADE IX JUNIOR HIGH SCHOOL STUDENTS (Pena Cendekia Insani, 2026)
The use of subordinating conjunctions in bold news texts is an important aspect that influences the cohesion and coherence of the text. However, the accuracy of the use of conjunctions in news texts remains a problem in writing journalistic wakana. The purpose of this study is to describe the errors in the use of subordinating conjunctions in news texts published on Detik.com. and to examine their potential use as Indonesian language learning resources. This study uses a qualitative descriptive approach with content analysis techniques. The research data consists of 30 news texts for the period January–April 2026 collected through documentation techniques with the reading and note-taking method. The results of the study showed 70 errors in the use of subordinating conjunctions including conjunctions of time, cause, condition, purpose, opposition, and comparison, with a dominance of inappropriate forms and incomplete clauses. These findings indicate that the use of conjunctions is not optimal in building text cohesion. Pedagogically, Detik.com news texts have the potential to be used as authentic teaching materials in Indonesian language learning in junior high schools to practice conjunction analysis, although it has not been implemented in schools.